2017
DOI: 10.1073/pnas.1706945114
|View full text |Cite
|
Sign up to set email alerts
|

Sirt7 promotes adipogenesis in the mouse by inhibiting autocatalytic activation of Sirt1

Abstract: Sirtuins (Sirt1-Sirt7) are NAD + -dependent protein deacetylases/ ADP ribosyltransferases, which play decisive roles in chromatin silencing, cell cycle regulation, cellular differentiation, and metabolism. Different sirtuins control similar cellular processes, suggesting a coordinated mode of action but information about potential cross-regulatory interactions within the sirtuin family is still limited. Here, we demonstrate that Sirt1 requires autodeacetylation to efficiently deacetylate targets such as p53, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
85
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 51 publications
3
85
0
Order By: Relevance
“…We have previously reported that Sirt7 interacts with and inhibits the Sirt1-mediated repression of PPARγ gene expression in adipocytes [19]. In contrast, Sirt7 promotes Sirt1 binding to rDNA together with DNA methyltransferase 1 (DNMT1) for induction of heterochromatin formation [21].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously reported that Sirt7 interacts with and inhibits the Sirt1-mediated repression of PPARγ gene expression in adipocytes [19]. In contrast, Sirt7 promotes Sirt1 binding to rDNA together with DNA methyltransferase 1 (DNMT1) for induction of heterochromatin formation [21].…”
Section: Resultsmentioning
confidence: 99%
“…Since Sirt1 positively regulates Suv39h1 activity [20] and Sirt1 becomes autodeacetylated at K230 and hyperactive in Sirt7 deficient cells [19], we speculated that hyperactivation of Sirt1 plays the decisive role for increased Suv39h1 activity in Sirt7 depleted cells. To corroborate this assumption, we expressed different combination of Sirt1, Sirt7 and Suv39h1 in HEK293T cells and monitored H3K9me3 levels.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations